(untitled) (Costos y Gestión, 2023)
The objective of this study was to find out if the revenue, received based on the SUS Table, is sufficient to cover the costs incurred, except for direct labor, in carrying out the Ergometric Test exam at the Onofre Lopes University Hospital (HUOL). In methodological terms, it is a case study, descriptive and with a qualitative approach. Informal interviews were carried out with the managers and employees of the service, and with those responsible for the operational and administrative support services. The results show that the unit cost calculated for carrying out the Ergometric Test at HUOL during 2018 was R 16.46 and that, compared to the transfer from SUS, there is a financial surplus in the amount of R 13, 54 per exam. During the research, it became evident that the cost management information controls in the institution are precarious, being done using several different systems. Finally, the study opened the discussion about the feasibility of providing health services and the possibility of sustainability and financial independence of the management company – Empresa Brasileira de Serviços Hospitalares – in relation to the subsidies received from the Union.